Nova ureditev stanovanjskih najemnih razmerij - Damjan, Matija (Podjetje in delo, 2017)
A housing rental contract is a legal transaction of private law, subject to special rules of housing legislation, whereas public policy elements are even more pronounced in non-profit housing arrangements. The article outlines certain proposals for the reform of housing rental regulation that were formulated in an expert study for the Ministry of the Environment and Spatial Planning. Due to the shortcomings in the implementation of the current regime of non-profit rental, it is proposed that the current non-profit rents be replaced with new instruments of cost rent and housing allowance. Important novelties would be the establishment of alternative dispute settlement mechanisms and the introduction of a court order for eviction.
Keywords: housing arbitration; housing rental agreement; najemnine; nepremičnine; neprofitno stanovanje; non-profit apartment; odpovedni razlogi; podnajem; rent, cancellation reasons; stanovanjska arbitraža; stanovanjske najemne pogodbe; sublease